التعدي على الإسم التجاري في القانون الجزائري - وحيدة قطار (My University, 2023)
Abstract : The trade name represents a great importance in society that many may overlook, although it is more important for merchants, when they rely on the effect that the trade name achieves in attracting the public to achieve their goals in their shops and promote their goods, and even profits, as it works to distinguish their shops from others. Other shops. This study included addressing the infringement of the trade name in Algerian law. This topic is considered important as it sheds light on how the trade name is infringed. The first chapter dealt with the nature of the trade name and the second chapter discussed the forms of legal protection for the trade name. ...................... الملخص: يشكل الاسم التجاري أهمية كبيرة في المجتمع قد يغفلها الكثير، بالرغم من انه يمثل أهمية أكثر بالنسبة للتجار، عند اعتمادهم على ما يحققه الاسم التجاري من تأثير في جذب الجمهور لتحقيق غاياتهم على محلاتهم التجارية وترويج بضائعهم، وحتى الأرباح، فهو يعمل على تمييز محلاتهم التجارية عن غيرها من المحال. حيث اشتملت هذه الدراسة على معالجة التعدي على الاسم التجاري في القانون الجزائري ويعتبر هذا الموضوع مهم اذ يتم القاء الضوء على كيفية التعدي على الاسم التجاري، وتناولت في الفصل الأول ماهية الاسم التجاري والفصل الثاني صور الحماية القانونية للاسم التجاري. .................. Résumé : The trade name represents a great importance in society, principally for merchants, when they rely on the effect that the trade name achieves in attracting customers, by achieving their goals in their shops and promote their goods, and even profits, as it works to distinguish their shops from others. The study included addressing, the nature of the trade name and the infringement to this name in Algerian law, sheding light on the forms of infringement and legal protection for the trade name.